Thermal Performance and Insulation Structure Design of ± 400kV Valve Side Bushing of Converter. Issue 1 (February 2021) - Shiling, Zhang; Lin, Gong
Abstract: The design features of inner and outer insulation structure of valve side bushing of ± 400kV converter transformer are representative. Its main insulation structure type and design method are basically consistent with those of ± 800kV converter transformer valve side bushing in China, but its design margin is lower than that of UHV converter transformer bushing, and the valve side bushing of ± 400kV converter transformer is used more in converter valve hall, so its insulation structure design and engineering should be It is necessary to analyze and discuss the insulation structure design of valve side bushing of ± 400kV converter transformer. In this paper, ± 400kV converter transformer valve side bushing insulation accident is analyzed in detail, from which the specific causes of insulation failure are summarized, providing reference for the design of internal and external insulation structure of converter transformer bushing. Based on this, this paper first analyzes the heating mechanism of the double guide rod structure of the converter bushing, gives the design size of the double guide rod structure from the theoretical analysis point of view, further optimizes the core insulation structure of the converter bushing, and gives the external insulation design scheme of the converter bushing from the perspective of internal and external insulation coordination, and checks and calculates the overall electric field distribution The radial electric field strength is controlled at 3.11kV/mm under working voltage and 0.51kV/mm under power frequency withstand voltage, which meet the requirements of electric field strength control in the design of ± 400kV converter bushing. Furthermore, the valve side bushing of the developed ± 400kV converter transformer is tested, and typical type tests such as power frequency dry withstand voltage test and partial discharge measurement, lightning impulse dry withstand voltage test and partial discharge measurement and temperature rise test are passed. The research results of this paper theoretically give the control requirements for the field strength design of the valve side bushing of converter transformer, and optimize the design size of its double guide rod structure, and develop a prototype to prove the effectiveness and reliability of the theoretical analysis. The above research results have good theoretical guidance value and practical significance for the insulation structure design and operation state maintenance of valve side bushing of ± 400 kV converter transformer.